Undergraduate Research as an Institutional Ethos-A Case Study Examining a Faculty Sponsored Research Symposium - Daniel M. Settlage; Latisha A. Settlage (Journal of the Scholarship of Teaching and Learning, 2021)
This article describes a high-impact, institutional approach of embedding undergraduate research. Using a regional, teaching-focused state university as a case study, the article documents the formation of a campus-wide annual undergraduate research symposium (URS) and examines changes in the institution’s culture toward student research. The URS has played the dual role of increasing undergraduate involvement with research and increasing faculty involvement in collaborative research. Key to the effectiveness of the URS is its openness to a wide variety of disciplines and promotion of faculty-student research mentoring. This case study provides background and direction to those wishing to replicate the transformative impact of integrating undergraduate research at their own institutions by forming a high-impact, campus-wide undergraduate research symposium.